Acute kidney injury through a metabolic lens: pathological reprogramming mechanisms and clinical translation potential - Gao, Jingli; Huang, Liuyifei; Zhang, Yuzhan; Wei, Lei; Yu, Zhixiang; Xing, Yan; Yuan, Jinguo; Ning, Xiaoxuan; Sun, Shiren (Frontiers in Physiology, 2025)
Acute kidney injury (AKI) represents a clinical syndrome with a bleak short-term prognosis, posing a high risk for the development of chronic kidney diseases and end-stage kidney disease. The underlying mechanisms of AKI are still not fully understood, and effective intervention strategies remain elusive. Enormous energy is required to meet the functional activity in hypermetabolic tubular epithelial cells (TECs), the most vulnerable cell types during AKI. Recent evidence has shed light on the reprogramming of metabolic pathways and the shift in energy substrates under pathological conditions. The reprogrammed metabolic pathway initially serves to compensate for energy shortages and supply substrates for cell repair during the early stages of AKI. However, sustained metabolic dysregulation tend to become detrimental for tubular repair and regeneration. Intriguingly, dynamic alterations in specific metabolites extend beyond their conventional roles as metabolic byproducts, actively participating in pathophysiology through multifaceted regulatory mechanisms during AKI. As yet, clinical therapy for AKI has not yet incorporated the intervention of metabolic disorders, highlighting a vast potential for extensive application. This review aims to summarize recent studies on the role of metabolic pathway reprogramming and metabolites in AKI, while discussing promising therapeutic strategies targeting metabolic reprogramming.